Safety and efficacy outcomes of left atrial posterior wall isolation compared to pulmonary vein isolation and pulmonary vein isolation with linear ablation for the treatment of persistent atrial fibrillation - Sutter, Joanne S.; Lokhnygina, Yuliya; Daubert, James P.; Bahnson, Tristram; Jackson, Kevin; Koontz, Jason I.; Sun, Albert Y.; Hegland, Donald D.; Thomas, Kevin L.; Jackson, Larry; Lewis, Robert; Granger, Christopher; et al. (The American heart journal, 2020)
Pulmonary wall isolation (PWI) is increasingly used as an adjunctive lesion set to compliment pulmonary vein isolation (PVI), especially in patients with persistent atrial fibrillation (AF). The objective was to compare outcomes of catheter ablation in patients with persistent AF undergoing PVI with and without adjunctive PWI. We performed a retrospective study of 558 patients who underwent de novo and repeat ablation for persistent AF. Subjects were matched using propensity score adjustments. Outcomes were freedom from recurrent atrial arrhythmia and adverse events. Among 558 patients who underwent ablation for persistent AF, 78 (14%) underwent PVI + PWI, 255 (46%) underwent PVI, and 225 (40%) underwent PVI + linear ablation. Stratified logistic regression analysis with propensity matching revealed higher odds of recurrent arrhythmia with PVI + PWI when compared to PVI (odds ratio [OR] 2.25, 95% CI 1.08-4.69, P = .030) and when compared to PVI + linear (OR 2.31, 95% CI 1.01-5.28, P = .048). Within the PVI + PWI group, 57.7% of subjects were in normal sinus rhythm at 6 months compared to 73.9% and 72.2% in PVI and PVI + linear groups, respectively. Adverse events were rare, with 19 events total identified across all groups. PVI + PWI does not appear to be as effective as PVI or PVI + linear ablation in reducing the recurrence of arrhythmia within 6 months of the index procedure in patients with persistent AF. A prospective, randomized controlled trial comparing these ablation techniques is needed to clarify the role of extensive substrate modification for treatment of persistent AF. PWI is increasingly used as an adjunctive lesion set to compliment PVI in patients with persistent AF. We performed a retrospective study of 558 patients who underwent de novo and repeat ablation for persistent AF to compare the outcomes between PVI with and without adjunctive PWI. We found an increased incidence in recurrence of AF and other atrial arrhythmias at 6 months in the PVI + PWI cohort compared to PVI with or without additional linear ablation. A prospective, randomized controlled trial comparing these ablation techniques is needed to clarify the role of extensive substrate modification for treatment of persistent AF.